PENERAPAN CLEANLINESS, HEALTH, SAFETY AND ENVIRONMENT (CHSE) HOMESTAY UNTUK KESELAMATAN WISATAWAN - Setyaningrum Nugraheni, Krisnawati; Dewi Maria, Aletta; Octafian, Ray (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
CHSE is made based on the Decree of the Minister of Health concerning Health Protocols in Public Places and Facilities in the Framework of Prevention and Control of Covid-19. The lack of knowledge from homestay managers about CHSE is the background to the need for training on the implementation of CHSE. Community service activities are collaboration of STIEPARI Semarang community service team with The Tourism and Sports Office of Pemalang Regency and conducted in a structured three stages of activities, starting with a survey on the level of understanding of CHSE to the homestay management community followed by focus group discussion activities and closed with training on CHSE. This community service is intended for homestay managers who are selected from four selected tourism villages, namely Penggarit Village, Surajaya Village, Kaliprau Village and Sikasur Village. The final hope of CHSE training is that homestay managers can help prevent and control Covid-19 for people in public places and facilities in order to prevent the occurrence of new epicenters or clusters during the pandemic and the main thing is the safety of tourists who stop by tourist villages during the pandemic